Quinidine in falciparum malaria. - White, N; Looareesuwan, S; Warrell, D; Chongsuphajaisiddhi, T; Bunnag, D; Harinasuta, T (1981)
Fourteen patients with falciparum malaria were successfully treated with oral quinidine. Twelve of these patients were followed for 35 days without recrudescence. In six patients the infection had already recrudesced after antimalarial treatment, which in two cases had included a full course of quinine. Quinidine caused no cardiotoxicity, although the electrocardiogram QTc interval was prolonged by more than 25% in four patients. In-vitro cultures from nine of these patients and a further seven patients with falciparum malaria showed that the minimum inhibitory concentration was consistently lower for quinidine than for quinine. Quinidine is an effective antimalarial drug for Plasmodium falciparum infections and may be more potent than quinine.